Penentuan Prioritas Pengurangan Limbah Dengan Metode Multi Attribute Utility Theory (Maut) Dan Technique Of Order Preference By Similiary To Ideal Solution (Topsis)(Studi Kasus : Ukm Batik Supriyarso) - Murti, Awaludin Nugroho Wisnu, Ida Nursanti, ST, M.Eng,Sc (2017)
Batik is one of the fabic's popular commodity and quite promising, but in it's development batik face the various challenges, one of them is the environmental aspect. This research was done in small and medium enterprises Supriarso in Kampoeng Batik Surakarta. First step in this research is describes the production process with Operation Process Chart (OPC), in the next step the waste that generated by the production process are identified and classified into solid waste non- hazardous and toxic substance, solid waste hazardous and toxic substance, wastewater and hazardous wastewater. The last step is determines the priority of waste should be reduced by the method of Multi Attribute Utility Theory (MAUT) and Technique of Order Preference by Similiarity to Ideal Solution (TOPSIS). The results of this study show a real picture of the production process in the form of Operation Process Chart (OPC), while the result of the calculation using Multi Attribute Utility Theory (MAUT) and Technique of Order Preference by Similiarity to Ideal Solution (TOPSIS) is similar to show that waste should be prioritized to be reduced is successively: liquid waste, solid waste hazardous and toxic substance, solid waste non- hazardous and toxic substance and the last one hazardous liquid waste.This research resulted in some of the proposed improvements to SMEs include the application of standard rules of production and waste water reduction be priority reductions Keywords: Batik, Waste, Priority